An empirical spectroscopic database for acetylene in the regions of 5850–6341 cm−1 and 7000–9415 cm−1. (December 2017) - Lyulin, O.M.; Campargue, A.
Abstract: Six studies have been recently devoted to a systematic analysis of the high-resolution near infrared absorption spectrum of acetylene recorded by Cavity Ring Down spectroscopy (CRDS) in Grenoble and by Fourier-transform spectroscopy (FTS) in Brussels and Hefei. On the basis of these works, in the present contribution, we construct an empirical database for acetylene in the 5850–9415 cm –1 region excluding the 6341–7000 cm −1 interval corresponding to the very strong ν1 +ν3 manifold. Our database gathers and extends information included in our CRDS and FTS studies. In particular, the intensities of about 1700 lines measured by CRDS in the 7244–7920 cm −1 region are reported for the first time together with those of several bands of 12 C 13 CH2 present in natural isotopic abundance in the acetylene sample. The Herman-Wallis coefficients of most of the bands are derived from a fit of the measured intensity values. A recommended line list is provided with positions calculated using empirical spectroscopic parameters of the lower and upper energy vibrational levels and intensities calculated using the derived Herman-Wallis coefficients. This approach allows completing the experimental list by adding missing lines and improving poorly determined positions and intensities. As a result the constructed line list includes a total of 11113 transitions belonging to 150 bands of 12 C2 H2 and 29 bands of 12 C 13 CH2 . For comparison the HITRAN database in the same region includes 869 transitions of 14 bands, all belonging to 12 C2 H2 . Our weakest lines have an intensity on the order of 10 –29 cm/molecule, about three orders of magnitude smaller than the HITRAN intensity cut off. Line profile parameters are added to the line list which is provided in HITRAN format. The comparison of the acetylene database to the HITRAN2012 line list or to results obtained using the global effective operator approach is discussed in terms of completeness and accuracy. Graphical abstract: fx1 Highlights: Previous and new results of six CRDS and FTS studies of acetylene are gathered. Vibrational transition dipole moment and Herman-Wallis coefficients are derived. An empirical database is constructed for 5851.5–6341 and 7001–9414 cm −1 intervals. It includes 11113 lines belonging to 150 bands of 12 C2 H2 and 29 bands of 12 C 13 CH2 . The database including line profile parameters is provided in HITRAN format.